A Novel Control Grid Interconnection of Renewable Energy Sources at the Distribution Level with Power-Quality Improvement Feature - Varma, K. Dinesh; Krishna, B.Vijaya; kumar, G.Anil (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Renewable energy resources (RES) are being increas-ingly connected in distribution systems utilizing power electronic converters. This paper presents a novel control strategy for achieving maximum benefits from these grid-interfacing inverters when installed in 3-phase 4-wire distribution systems. The inverter is controlled to perform as a multi-function device by in corpo-rating active power filter functionality. The inverter can thus be utilized as: 1) power converter to inject power generated from RES to the grid, and 2) shunt APF to compensate current un bal-ance, load current harmonics, load reactive power demand and load neutral current. All of these functions may be accomplished either individually or simultaneously. With such a control, the combination of grid-interfacing inverter and the 3-phase 4-wire linear/non-linear unbalanced load at point of common coupling appears as balanced linear load to the grid. This new control concept is demonstrated with extensive MATLAB/Simulink simu-lation .